(untitled) (Global Journal of Science Frontier Research, 2014)
On the basis of the strict solution of the classical problem of two bodies, it is shown that the interaction of an electron with the proton occurs by the law of binomial potential. With regard for this law, we obtain a formula for the calculation of the angles of deviation of electrons at the scattering by protons. The formula allows one to find the angles for the energies of electrons from several eV to hundreds of MeV and for the impact parameters down to 10-13 cm. Generally, we may assert that the classical mechanics with the binomial potential can sufficiently exactly represent any phenomena in the microworld.